Crystal structure of the complex of DNA with the C‐terminal domain of TYE7 from Saccharomyces cerevisiae. Issue 10 (4th October 2021) - Gui, Wei; Xue, Lu; Yue, Jian; Kuang, Zhiling; Jin, Yuping; Niu, Liwen
Abstract : TYE7 has abundant physiological functions. Here a complex of DNA with the C‐terminal domain of TYE7 from Saccharomyces cerevisiae has been determined. Detailed structural analysis shows that Arg193 in TYE7 is unusual compared with Arg193 in other similar structures. Abstract : TYE7, a bHLH (basic helix–loop–helix) transcription factor from Saccharomyces cerevisiae, is involved in the regulation of many genes, including glycolytic genes. Meanwhile, accumulating evidence indicates that TYE7 also functions as a cyclin and is linked to sulfur metabolism. Here, the structure of TYE7 (residues 165–291) complexed with its specific DNA was determined by X‐ray crystallography. Structural analysis and comparison revealed that His185 and Glu189 are conserved in base recognition. However, Arg193 is also involved in base recognition in the structures that were compared. In the structure in this study, Arg193 in chain A has two conformations and makes a salt bridge with the phosphate backbone structure. In addition, a series of corresponding electrophoretic mobility shift assays were performed to better understand the DNA‐binding mechanism of the bHLH domain of TYE7.